Feasibility of polymer gel-based measurements of radiation isocenter accuracy in magnetic fields - Dorsch, Stefan; Mann, Philipp; Lang, Clemens; Runz, Armin; Karger, Christian (Physics in medicine and biology, 2018)
For conventional irradiation devices, the radiation isocenter accuracy is determined by star shot measurements on films. In magnetic resonance (MR)-guided radiotherapy devices, the results of this test may be altered by the magnetic field and the need to align the radiation and imaging isocenter may require a modification of measurement procedures. Polymer dosimetry gels (PG) may offer a way to perform both, the radiation and imaging isocenter test, however, first it has to be shown that PG reveal results comparable to the conventionally applied films. Therefore, star shot measurements were performed at a linear accelerator using PG as well as radiochromic films. PG were evaluated using MR imaging and the isocircle radius and the distance between the isocircle center and the room isocenter were determined. Two different types of experiments were performed: i) a standard star-shot isocenter test and (ii) a star shot, where the detectors were placed between the pole shoes of an experimental electro magnet operated either at 0 T or 1 T. For the standard star shot, PG evaluation was independent of the time delay after irradiation (1 h, 24 h, 48 h and 216 h) and the results were comparable to those of film measurements. Within the electro magnet, the isocircle radius increased from 0.39 ± 0.01 mm to 1.37 ± 0.01 mm for the film and from 0.44 ± 0.02 mm to 0.97 ± 0.02 mm for the PG-measurements, respectively. The isocenter distance was essentially dependent on the alignment of the magnet to the isocenter and was between 0.12 ± 0.02 mm and 0.82 ± 0.02 mm. The study demonstrates that evaluation of the PG directly after irradiation is feasible, if only geometrical parameters are of interest. This allows using PG for star shot measurements to evaluate the radiation isocenter accuracy with comparable accuracy as with radiochromic films.
Gesehen am 24.05.2019